PENGUATAN PENDIDIKAN KARAKTER MENGGUNAKAN MODEL PEMBELAJARAN TRIPRAKORO UNTUK ANAK USIA SEKOLAH DASAR DI KECAMATAN PESANGGARAN BANYUWANGI - Finali, Zetti; Mahmudi, Kendid; Masrifah, Siti Masrifatul (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic has had a tremendous impact, especially for education in Indonesia. Formal education, which usually uses an online or face-to-face learning system, during the pandemic must change to an online learning system. In Pesanggaran Subdistrict, Banyuwangi Regency, online learning using electronic devices cannot run well. This is known from the results of an interview with the Education Unit Work Area Coordinator (Korwilker Satdik) of Pesanggaran Banyuwangi District on September 30, 2021. This community service uses training, mentoring, and evaluation methods. This activity will be carried out in the Sumberagung cluster and located at SDN 6 Sumberagung. Learning in elementary schools during the COVID-19 pandemic was carried out with a network or online system. Online learning is quite difficult to cover the affective domain. The affective domain is a domain related to students' attitudes, values, feelings, or emotions. At the time of easing PPKM and learning in schools can be done with limited face-to-face, it is very necessary activities that can support the development of the affective domain.